POLITIK BAHASA DAN BAHASA POLITIK (Bahasa dalam Praksis Politik di Indonesia) - Rahardjo, Mudjia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
At a glance, there is no relation between language and politics. In Jae:, both and politics have mutual and equal relationship. Language is not only a means of political communication, but also a medium of political practice. As a symbolic reality, language can be used as a means to understand pm1Â·er dynamics and hove power works. Realizing the important role of language in political practice, every regime uses it as a significant instrument to carry out power consolidation by creating certain political idioms. Therefore, controlling public awareness and social collective memory through a symbolic reality always becomes a part of agenda of the authority to maintain their power. It is, therefore, eiÂ·ery change of regime is always followed byÂ the changes of new terms based on the ideology to struggle.